Method for manufacturing 3C-SiC photocatalyst and method for producing hydrogen
A modified thermal carbon reduction method using silicon oxide, carbon, and aluminum compounds with a specific molar ratio enhances 3C-SIC photocatalysts' hydrogen production and stability, addressing high-cost and low-productivity issues in existing methods, and achieving efficient hydrogen generation.
Patent Information
- Application Number
- JP2021002833
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-12
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2041-01-12
AI Technical Summary
The existing methods for producing 3C-SIC photocatalysts, such as Chemical Vapor Deposition (CVD) and thermal carbon reduction, result in high manufacturing costs and low productivity, while the photocatalysts produced by thermal carbon reduction have low hydrogen production ability and high defect densities, limiting their practical application in hydrogen generation.
A modified thermal carbon reduction method is employed, involving a mixture of silicon oxide, carbon, and aluminum compounds with a specific molar ratio (AL/SI ≥ 0.04) to produce 3C-SIC, followed by post-processing to remove impurities, enhancing hydrogen production capacity and stability.
The method produces 3C-SIC photocatalysts with improved hydrogen production ability and stability, capable of generating hydrogen efficiently even under low solar densities, reducing costs compared to CVD methods.
Smart Images

Figure 0007623569000002 
Figure 0007623569000003 
Figure 0007623569000004
Abstract
Description
[Technical field]
[0001] The present application discloses a method for producing a 3C-SiC photocatalyst, in particular a method for producing a 3C-SiC photocatalyst suitable for water decomposition by light irradiation, and a method for producing hydrogen using 3C-SiC produced by this method. [Background technology]
[0002] The technology of decomposing organic matter or water using photocatalysts is widely known. In particular, water decomposition using photocatalysts is promising as a renewable energy generation technology because it can convert solar energy into hydrogen energy, for example. Titanium oxide (TiO2) and other semiconductor materials have been widely used for this purpose, but they have a problem of low energy conversion efficiency.
[0003] One of the reasons for this is that the forbidden band width (hereafter referred to as the "band gap") of titanium oxide is relatively wide, at approximately 3.0 eV. When light is irradiated onto a semiconductor material in contact with H2O, electrons inside the semiconductor are excited from the valence band to the conduction band, generating electron-hole pairs. The electrons are transported to the surface of the semiconductor material and are transported to the H + The semiconductor material reduces the photons to generate H2 gas. On the other hand, the holes are also transported to the surface of the semiconductor material, and then oxidize H2O to generate O2 gas. At this time, in order for electrons to be excited in the semiconductor material, that is, for electron-hole pairs to be generated, it is necessary to irradiate the semiconductor material with light with energy greater than the forbidden band width. Therefore, in the case of TiO2, which has a band gap of approximately 3.0 eV, light with a wavelength of approximately 400 nm or less is absorbed and electrons are generated. However, considering the components of sunlight, if only photons of 400 nm or less are used to generate hydrogen, the energy conversion efficiency is only about 2% at most.
[0004] Therefore, it has been proposed to use single-crystal 3C-SiC as a photocatalyst for the purpose of water splitting (Patent Document 1). 3C-SiC has a band gap of 2.23 eV and is capable of absorbing light of approximately 550 nm or less and generating electron-hole pairs. Furthermore, the lower end of the conduction band of 3C-SiC is H2 / H + The redox potential of SiO2 is lower than that of H2O / O2, and the upper end of the valence band is higher than the redox potential of H2O / O2. This makes this material suitable for use as a photocatalyst in water splitting.
[0005] However, 3C-SiC has a crystal structure that is more stable at low temperatures than other polymorphs such as 4H-SiC and 6H-SiC, making it difficult to grow bulk single crystals by the sublimation recrystallization method, which is a method for manufacturing 4H-SiC and 6H-SiC. Therefore, in order to obtain 3C-SiC as a single crystal or polycrystalline wafer, it is common to grow 3C-SiC on a foreign substrate using the chemical vapor deposition (CVD) method. The foreign substrate used here is often silicon (Si) or a foreign polymorph (4H-SiC or 6H-SiC) when manufacturing a single crystal.
[0006] On the other hand, in consideration of the operability when generating hydrogen from water using a photocatalyst, it is desirable for the photocatalyst to be in the form of a plate. A plate shape is, for example, a panel shape like a solar cell module. Such panels are made by molding a single crystal or polycrystalline wafer, or by coating a powder.
[0007] As mentioned above, 3C-SiC single crystal or polycrystalline wafers are produced by the CVD method. However, there are problems with high production costs and low productivity in order to ensure a practical amount of hydrogen production as a photocatalyst.
[0008] On the other hand, although not for photocatalytic applications, a silicothermal carbothermal reduction method is known as a simple and inexpensive method for producing 3C-SiC powder (eg, Non-Patent Document 1). [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2016-145141 A [Non-patent literature]
[0010] [Non-Patent Document 1] Journal of the Ceramic Society of Japan 99 [9] 768 (1991) Summary of the Invention [Problem to be solved by the invention]
[0011] As mentioned above, single crystal or polycrystal 3C-SiC produced by CVD has problems of high manufacturing cost and low productivity. In addition, 3C-SiC produced by carbothermal reduction is used as a raw material for sintering ceramics, but because of its high stacking fault density, it is thought that its hydrogen production capacity is low even if it is used as a photocatalyst, and thus it has not been used as a photocatalyst until now. In this regard, there is room for improvement in terms of improving the hydrogen production capacity of 3C-SiC photocatalysts obtained by carbothermal reduction. [Means for solving the problem]
[0012] In the production of 3C-SiC by the carbothermal reduction method, a silicon-containing oxide such as silica is mixed with a carbon source such as carbon black to obtain a mixture, and the mixture is heated to cause a carbothermal reduction reaction to generate 3C-SiC. However, as mentioned above, it has been found that 3C-SiC produced by the conventional carbothermal reduction method as disclosed in Non-Patent Document 1, which is produced as a raw material for sintering ceramics, has low hydrogen generation ability as a photocatalyst.
[0013] Therefore, the inventors have intensively studied improvements to the carbothermal reduction method and found that, when 3C-SiC is produced by mixing a certain amount or more of an aluminum-containing compound in addition to the silicon-containing oxide and the carbon source in the above mixture, a 3C-SiC photocatalyst with higher hydrogen generation capacity than that of a 3C-SiC photocatalyst produced by the conventional carbothermal reduction method can be produced. It is presumed that the hydrogen generation capacity is improved by incorporating Al in the aluminum-containing compound into the SiC crystal, i.e., by doping.
[0014] In addition, it was found that the 3C-SiC photocatalyst produced by the above manufacturing method produces more hydrogen even when the solar light density is low, compared to when 3C-SiC produced by the conventional carbothermal reduction method is used as a photocatalyst. A hydrogen production device using a photocatalyst that utilizes solar light is assumed to be, for example, in the form of a panel. In this case, it is expected that the sunlight is not always evenly applied to the photocatalyst, and the light intensity (sunlight density) will decrease depending on factors such as the time of day, weather, and season. In other words, it is desirable for a photocatalyst to be able to produce more hydrogen even when the solar light density is low. In this respect, the 3C-SiC photocatalyst produced by the above manufacturing method is also preferable from a practical standpoint.
[0015] Based on the above findings, the present application provides, as a means for solving the above problems, Mixing a silicon-containing oxide, a carbon source, and an aluminum-containing compound to obtain a mixture; and heating the mixture to effect a carbothermal reduction reaction to obtain a product comprising 3C-SiC; Including, The molar ratio Al / Si of Al and Si contained in the mixture is 0.04 or more. Manufacturing method of 3C-SiC photocatalyst Disclose.
[0016] In the method for producing a 3C-SiC photocatalyst of the present disclosure, the molar ratio Al / Si may be 0.08 or more.
[0017] In the method for producing a 3C-SiC photocatalyst of the present disclosure, the mixture may be heated to a temperature of 1400°C or higher and 1700°C or lower.
[0018] The method for producing a 3C-SiC photocatalyst of the present disclosure may include, after the carbothermal reduction reaction, heating the product in an oxidizing atmosphere to remove elemental carbon contained in the product.
[0019] In the method for producing a 3C-SiC photocatalyst of the present disclosure, Al2O3 may be used as the aluminum-containing compound.
[0020] In the method for producing a 3C-SiC photocatalyst of the present disclosure, SiO2 may be used as the silicon-containing oxide.
[0021] In the method for producing a 3C-SiC photocatalyst of the present disclosure, carbon black may be used as the carbon source.
[0022] In addition, the present application provides the following as a means for solving the above problems: A method for producing hydrogen using a 3C-SiC photocatalyst produced by the method of the present disclosure, comprising: producing hydrogen by irradiating the 3C-SiC photocatalyst with light while the 3C-SiC photocatalyst is in contact with water and decomposing the water. Disclose. Effect of the Invention
[0023] According to the present invention, a photocatalyst having a higher hydrogen generation capacity than that obtained by using 3C-SiC powder produced by the conventional carbothermal reduction method and used as a ceramic raw material can be produced by utilizing a simple and inexpensive carbothermal reduction method rather than an expensive production method such as a CVD method. [Brief description of the drawings]
[0024] [Figure 1] 1 shows a schematic diagram of an example of a method for synthesizing a 3C-SiC photocatalyst. [Diagram 2]An example of a powder XRD pattern of a 3C-SiC photocatalyst is shown. [Diagram 3] An example of a hydrogen production device using a 3C-SiC photocatalyst is shown diagrammatically. [Figure 4] The relationship between the molar ratio Al / Si in the mixture and the hydrogen production rate over the synthesized 3C-SiC photocatalyst is shown. [Diagram 5] The figure shows the relationship between light irradiation time and the amount of hydrogen produced for water splitting performed using the catalyst of the embodiment by irradiating light with a light intensity of 50% and water splitting performed by irradiating light with a light intensity of 100%. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Hereinafter, one embodiment of the present invention will be described in detail.
[0026] 1. Photocatalyst manufacturing method The method for producing a 3C-SiC photocatalyst by the carbothermal reduction method according to the present embodiment will be described. The method for producing a 3C-SiC photocatalyst according to the present embodiment includes mixing an oxide containing silicon, a carbon source, and a compound containing aluminum to obtain a mixture, and heating the mixture to cause a carbothermal reduction reaction to obtain a product containing 3C-SiC. Here, in the present embodiment, it is important that the molar ratio Al / Si of Al and Si contained in the mixture is 0.04 or more.
[0027] 1.1 Silicon-containing oxides As described above, in this embodiment, 3C-SiC is produced through a carbothermal reduction reaction. In order to cause such a reaction, silicon takes the form of an oxide before the carbothermal reduction reaction. Examples of oxides containing silicon include SiO2, silicate minerals such as aluminum silicate, and SiAlON. In particular, when SiO2 is used as an oxide containing silicon, the desired carbothermal reduction reaction is easily caused. In addition, according to the knowledge of the present inventor, when SiO2 is used, even if SiO2 remains in the product after the carbothermal reduction reaction, there is also an advantage that SiO2 can be easily removed from the product by an acid containing hydrofluoric acid.
[0028] The shape of the oxide containing silicon is not particularly limited. The shape of the oxide containing silicon can be selected according to the shape of the desired 3C-SiC. For example, in addition to particulate (powdered), it may be a single crystal, an amorphous body, or a molded body obtained by previously processing the powder by pressing or the like. Here, the powder refers to a solid aggregate having an average particle size of 1 mm or less when the particle size distribution is measured by wet laser diffraction. When the oxide containing silicon is particulate, the particles may be primary particles or secondary particles formed by agglomeration of primary particles. When the oxide containing silicon is particulate, the average particle size (D50) may be, for example, 10 nm or more, 100 nm or more, 1 μm or more, 10 μm or more, or 100 μm or more, or 1 mm or less, 500 μm or less, or 300 μm or less. When the oxide contains silicon, it is considered that the above-mentioned carbothermal reduction reaction is more efficient. The average particle size D50 in the present application is the particle size (median size) at an integrated value of 50% in the volume-based particle size distribution determined by a laser diffraction / scattering method.
[0029] 1.2 Carbon source In this embodiment, the carbon source is used as a raw material for SiC and also as a reducing agent for silicon-containing oxides. For such purposes, the carbon source may be a material containing carbon as a main component. As the carbon source, for example, simple carbon such as graphitic carbon or non-graphitic carbon (carbon black, glassy graphite, etc.) may be used. According to the findings of the present inventors, it is easy to cause the desired carbothermal reduction reaction, particularly when carbon black is used as the carbon source. In addition, when carbon black is used, there is an advantage that it can be easily removed by oxidation or the like if it is mixed into the product unreacted.
[0030] The shape of the carbon source is not particularly limited. From the viewpoint of more efficiently generating the carbothermal reduction reaction, the carbon source may be particulate. When the carbon source is particulate, the average particle diameter may be, for example, 10 nm or more or 40 nm or more, and 150 nm or less or 100 nm or less. The average particle diameter of the particles of the carbon source other than carbon black (for example, particulate graphite) is the particle diameter (median diameter) D50 at an integrated value of 50% in the volume-based particle size distribution obtained by a laser diffraction / scattering method. The average particle diameter of carbon black means the average diameter (average value of circle equivalent diameters) calculated by measuring the smallest spherical (having a contour due to microcrystals and inseparable) component constituting the carbon black aggregate with an electron microscope (Carbon Black Yearbook, 60th Anniversary Issue, No. 58, 2008, Carbon Black Association, p. 82). In general, the smallest spherical particles constituting the carbon black aggregate cannot be separated and exist in a fused state.
[0031] When carbon black is used as the carbon source, it is preferable to use powdered carbon black, but carbon black in the form of aggregated powder may be pulverized and used. Carbon black is classified into various types such as acetylene black, ketjen black, and thermal black depending on the production method and raw materials, but the type of carbon black that can be used in the present embodiment is not particularly limited.
[0032] 1.3 Aluminum-containing compounds In this embodiment, as the compound containing Al, a material that does not melt at the synthesis temperature of 3C-SiC or a material that is difficult to react with the reaction vessel at the synthesis temperature of 3C-SiC and can prevent damage to the reaction vessel can be selected. For example, alumina (aluminum oxide: Al2O3) having a high melting point may be used. In this case, Al2O3 mixed in the mixture may be reduced upon heating by contacting with a carbon source, and may become gaseous or liquid Al or Al compounds. When SiC is synthesized, these Al or Al resulting from Al compounds may be incorporated into the crystals of SiC particles and doped. The compound containing Al is not limited to alumina, and other compounds containing Al such as aluminum carbide (Al4C3), aluminum silicate, and SiAlON may be used. However, according to the knowledge of the present inventor, it is particularly easier to dope 3C-SiC with aluminum when Al2O3 is used as the compound containing aluminum.
[0033] The shape of the aluminum-containing compound is not particularly limited, but when the compound is particulate, it is considered that doping of aluminum into 3C-SiC is more efficient. When the aluminum-containing compound is particulate, the particles may be primary particles or secondary particles formed by agglomeration of primary particles. The average particle size (D50) may be, for example, 20 nm or more or 50 nm or more, and 500 μm or less or 100 μm or less.
[0034] 1.4 Mixtures In this embodiment, the silicon-containing oxide, the carbon source, and the aluminum-containing compound are mixed to obtain a mixture. The mixing method is not particularly limited, and the mixture may be mixed by hand using an agate mortar or the like, or may be mixed mechanically using a mixing device such as a ball mill. The mixing time is also not particularly limited.
[0035] The mixing ratio of the oxide containing silicon, the carbon source, and the compound containing aluminum may be such that the molar ratio Al / Si is 0.04 or more. In particular, when the molar ratio Al / Si is 0.08 or more, 3C-SiC having better photo-water splitting activity is easily obtained. The upper limit of the molar ratio Al / Si is not particularly limited, but from the viewpoint of leaving as little unnecessary aluminum compound as possible after the carbothermal reduction reaction, the molar ratio Al / Si may be 0.40 or less or 0.20 or less. In addition, the molar ratio C / Si of C and Si contained in the mixture is not particularly limited. From the viewpoint of causing the carbothermal reduction reaction to occur sufficiently, the molar ratio C / Si of C and Si contained in the mixture may be 3.0 or more or 3.1 or more. In addition, from the viewpoint of leaving as little unnecessary carbon as possible after the carbothermal reduction reaction, the molar ratio C / Si may be 4.0 or less, 3.9 or less, or 3.8 or less. It should be noted that by including a larger amount of C in the mixture, the compound containing aluminum can also be reduced by C.
[0036] Thus, in this embodiment, the Al / Si molar ratio in the mixture used for synthesizing 3C-SiC is adopted as an index for doping Al into 3C-SiC. The mass of the Al-containing compound in the mixture is calculated according to the purity of the Al-containing compound, and the amount of substance (molar number) of Al is calculated. Similarly, for the silicon-containing compound, the amount of substance of Si in the mixture is calculated from the purity and mass. The ratio is taken as the Al / Si ratio. When a commercially available product is used as the silicon-containing oxide or aluminum-containing compound, the above molar ratio Al / Si may be specified using the purity indicated on the label of the commercially available product. When the purity is unknown, the purity or molar ratio may be determined, for example, from the intensity of powder XRD.
[0037] 1.5 Carbothermal reduction As disclosed in Non-Patent Document 1, in a method for synthesizing SiC called carbothermal reduction, it is known that SiC is produced by the reactions of the following formulas (1) and (2). SiO2(s)+C(s)=SiO(g)+CO(g)...(1) SiO(g)+2C(s)=SiC(s)+CO(g)...(2)
[0038] In this embodiment, the mixture is heated to cause a carbothermal reduction reaction as shown in reaction formula (1) or (2) to obtain a product containing 3C-SiC. The heating method is not particularly limited, and heating may be performed using a known heating furnace. As a reaction vessel during heating, for example, a crucible-shaped vessel made of graphite or a high melting point metal can be used, but it is not necessarily limited to this as long as it is not damaged at the synthesis temperature of SiC. In this embodiment, when SiC is synthesized, Al contained in the mixture is incorporated into the crystal of SiC, and Al-doped SiC can be synthesized. Here, the crystal structure of SiC, i.e., polymorphism, can be controlled by the temperature (heating temperature) during the carbothermal reduction reaction. Specifically, it is known that 3C-SiC is a phase that is relatively thermally stable compared to different polymorphs at approximately 1700°C or less (Ceramics Association Journal 77 [4] 1969 133). Therefore, the temperature at which the mixture is heated may be, for example, 1700°C or lower, preferably 1650°C or lower, more preferably 1600°C or lower. In addition, when the heating temperature is low, the reaction rate is slow. In this respect, the temperature at which the mixture is heated may be 1400°C or higher, preferably 1450°C or higher. Until all the Si in the mixture reacts to become SiC, the amount of SiC synthesized increases depending on the heating time. Therefore, the optimal heating time differs depending on the amount of Si contained in the mixture. The optimal heating time can also be determined by confirming the presence of oxides (e.g., SiO2) containing silicon remaining after synthesis. The heating atmosphere may also be any atmosphere that can cause a carbon thermal reduction reaction. For example, heating may be performed in an inert gas atmosphere. The inert gas is preferably Ar or He. Other inert gases include N2, but it is known that nitrogen acts as a dopant by being incorporated into the crystal and acting as an n-type dopant. Therefore, it is better to avoid using N2 because there is a risk of inhibiting the doping effect of Al, which is a p-type dopant.
[0039] 1.6 Products In this embodiment, a product containing 3C-SiC is obtained. Here, in this embodiment, 3C-SiC can be doped with aluminum. Whether 3C-SiC is doped with aluminum can be determined, for example, by observing the color of 3C-SiC contained in the product. That is, as far as the inventors have confirmed, when 3C-SiC not containing aluminum and 3C-SiC doped with aluminum are compared side by side, both are gray, but the doping of Al is confirmed because the light and dark are different. Note that only a very small amount of aluminum is doped into 3C-SiC. Therefore, there is no substantial change in the position of the diffraction peak by, for example, XRD before and after doping.
[0040] 1.7 Post-treatment and reduction processes As described above, in this embodiment, a product containing 3C-SiC is obtained by heating a predetermined mixture to cause a carbothermal reduction reaction. Here, not all of the silicon-containing oxides, carbon sources, and Al-containing compounds used as raw materials necessarily react, and silicon-containing oxides, elemental carbon, and aluminum-containing compounds may remain together with the synthesized 3C-SiC. Therefore, in order to remove these, a post-treatment process or a reduction process may be performed. Here, in this embodiment, the post-treatment process refers to a process for removing elemental carbon and silicon-containing oxides.
[0041] The manufacturing method according to the present embodiment may include heating the product in an oxidizing atmosphere after the carbothermal reduction reaction to remove elemental carbon contained in the product. For example, in order to remove elemental carbon, the product obtained by the manufacturing method according to the present embodiment may be introduced into a heating furnace in which oxygen is present, such as an atmospheric furnace, and heated to oxidize and remove elemental carbon. More specifically, the product may be placed in a quartz container and removed at a temperature of about 700°C to 1000°C in a temperature-controlled atmospheric furnace. In this temperature range, the oxidation reaction of the surface of SiC can be suppressed. Note that the "removal" of elemental carbon is not limited to complete removal, and it is sufficient that the amount of elemental carbon in the product is reduced. The same applies to the removal of oxides containing silicon (e.g., SiO2) and compounds containing aluminum (e.g., Al2O3) described below.
[0042] In order to remove elemental carbon, the product is heated in an oxidizing atmosphere, and as a result, SiO2 may be inevitably formed on the surface of SiC in the product. In this case, in order to remove SiO2, an acid cleaning treatment may be performed using a mixed acid of hydrofluoric acid and nitric acid. The volume ratio of hydrofluoric acid to nitric acid in the mixed acid is not particularly limited, and may be, for example, 1:1 to 1:2.
[0043] When Al2O3 is used as the aluminum-containing compound, a reduction step may be performed after the above-mentioned post-treatment step. In the reduction step, for example, the reaction product after the post-treatment step is mixed with a carbon source (e.g., carbon black), and then a heat treatment similar to the heat treatment in the above-mentioned carbothermal reduction reaction is performed to reduce the Al2O3 remaining in the reaction product. Thereafter, a treatment to remove elemental carbon and SiO2 may be performed again in the same manner as in the above-mentioned post-treatment.
[0044] In this embodiment, it is better to remove elemental carbon that may chemically react in the photocatalytic reaction. On the other hand, there is no concern that oxides containing silicon (e.g., SiO2) or compounds containing aluminum (e.g., Al2O3) will inhibit the photocatalytic reaction from the viewpoint of band gap. However, when SiO2 is formed on the SiC surface, it is preferable to perform the above-mentioned removal process since there is a possibility that it will inhibit the photocatalytic reaction. Furthermore, since the relative amount of SiC in the reaction product is reduced if Al2O3 remains, it is desirable to remove it as much as possible, but removal of Al2O3 is not necessarily required. According to the knowledge of the present inventors, the product obtained by the manufacturing method according to this embodiment exhibits high water decomposition activity as a photocatalyst even if it contains a large amount of Al2O3 together with 3C-SiC.
[0045] 2. Hydrogen production method using photocatalysis A hydrogen production method using the photocatalyst powder according to the present embodiment will be described. The hydrogen production method according to the present embodiment is a hydrogen production method using a 3C-SiC photocatalyst produced by the photocatalyst production method according to the present embodiment described above, and is characterized in that the 3C-SiC photocatalyst is brought into contact with water and irradiated with light to decompose water, thereby producing hydrogen.
[0046] The form of the photocatalyst during hydrogen production is not particularly limited. For example, a particulate photocatalyst may be dispersed in water and irradiated with light to cause a water splitting reaction to produce hydrogen, or a photocatalyst may be formed into a panel, and the panel may be immersed in water and irradiated with light to cause a water splitting reaction to produce hydrogen, or a photocatalyst may be used to form an electrode for water splitting, and the electrode may be immersed in water and irradiated with light to perform water electrolysis. The container for holding water and the photocatalyst may be any container made of a light-transmitting material, and examples of such containers include resins such as acrylic resins and polyvinyl chloride resins, glass, natural quartz, synthetic quartz, and inorganic materials such as soda lime glass.
[0047] In particular, when hydrogen is produced on a large scale by a photochemical water splitting reaction, it is preferable to use the electrode for photochemical water splitting reaction from the viewpoint of promoting the water splitting reaction by applying a bias. In another embodiment, the 3C-SiC photocatalyst can completely split water by itself, and a laminate having a photocatalyst layer containing the photocatalyst on a substrate or a composite containing the photocatalyst can be placed in water without applying a bias. In this case, processing and handling are easy, maintenance is easy, and the cost of an artificial photosynthesis device that requires a large area can be reduced. In other words, an industrially advantageous water splitting device, oxygen generation device, hydrogen generation device, or artificial photosynthesis system can be obtained.
[0048] Sunlight can be used as the light source. Note that sunlight is not always equally irradiated onto the photocatalyst, and it is expected that the light intensity (sunlight density) will decrease depending on factors such as the time of day, weather, and season. In other words, it is desirable for the photocatalyst to be able to produce more hydrogen even when the sunlight density is low. In this regard, the 3C-SiC photocatalyst according to this embodiment produces more hydrogen even when the sunlight density is low, compared to when 3C-SiC produced by the conventional silicocarbothermal reduction method is used as the photocatalyst. Alternatively, artificial light, not natural light, may be used as the light source. EXAMPLES
[0049] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples.
[0050] 1. Example 1 As described below, the 3C-SiC photocatalyst was produced through three processes: a synthesis process including mixing and heating (thermal carbon reduction), a post-treatment process aimed at removing carbon components and SiO2, and a reduction process aimed at removing Al2O3.
[0051] 1.1 Synthesis process As shown in Table 1 below, 80 g of SiO2 powder (FUJIFILM Wako Pure Chemical Co., Ltd., 199-00625) as an oxide containing silicon, 50 g of carbon black (Nippon Steel Carbon, HTC#20) as a carbon source, and 5.44 g of Al2O3 powder (FUJIFILM Wako Pure Chemical Co., Ltd., 012-0196) as a compound containing aluminum were put into an agate mortar and mixed so that the color of the raw material powder was visually uniform to obtain a mixture 1. Thereafter, as shown in FIG. 1, the mixture 1 was put into a graphite crucible 2 (Shin-Nihon Techno Carbon Co., Ltd., IGS-743), which was placed inside a carbon molded insulation material 3, and introduced into a chamber 5 of a high-frequency induction heating furnace (Daiichi Kiden Co., Ltd., S08-5817) equipped with a high-frequency induction coil 4. Next, the inside of the chamber 5 was heated to 1000° C. using a rotary pump and an oil diffusion pump. -3 The chamber was evacuated to a pressure in the Pa range. Next, inert Ar gas (99.99%) was introduced to achieve atmospheric pressure, and heating was started. The temperature was raised from room temperature to the synthesis temperature of 1500°C over a period of 2 hours, and then the chamber was kept at 1500°C for 40 hours. The chamber was then cooled to room temperature over a period of 4 hours to obtain a product containing a photocatalyst.
[0052] 1.2 Post-processing Next, the product containing the photocatalyst was collected from the graphite crucible, sieved with a 180 μm mesh sieve, and then the powder sieved with a 75 μm mesh was collected. Next, the sieved powder was placed in a 300 ml quartz beaker and heated at 700 °C for 10 hours in an electric furnace (Advantec, KM-280) to remove unreacted carbon components remaining in the product. Next, hydrofluoric acid (Kishida Chemical, concentration 46% special grade) and nitric acid (Kishida Chemical, concentration 60% special grade) were mixed in a volume ratio of 1:1 to 1:2, and SiO2 in the product was dissolved and removed. After that, it was washed several times with ion-exchanged water, and then suction filtration was performed using a 0.1 μm hydrophilic PTFE membrane filter (Advantec), and the powder containing the photocatalyst was collected.
[0053] Next, a reduction process was carried out to remove Al2O3. The molar ratio of the powder after the post-treatment process was calculated assuming that all of the powder after the post-treatment process was Al2O3, and 5.69 g of carbon black (Nippon Steel Carbon, HTC#20) as a carbon source was mixed with the powder after the post-treatment process in an agate mortar so that the color of the powder was uniform to the naked eye, so that the molar ratio was approximately four times that amount. The mixture was then placed in a crucible made of graphite of the same type as that used in the synthesis of the photocatalyst powder, and the mixture was subjected to the same heat treatment as in the synthesis using a high-frequency induction heating furnace, in order to reduce the amount of Al2O3 remaining in the powder after synthesis.
[0054] Next, similarly to the treatment of the powder after synthesis, residual carbon components were removed in an electric furnace, and residual SiO2 was removed with an acid, followed by suction filtration to recover the photocatalyst powder according to Example 1.
[0055] 1.3 Phase identification by powder XRD measurement The crystal structure of the SiC photocatalyst synthesized through the above process was identified by the powder XRD method. Specifically, an X-ray diffractometer (Rigaku, fully automatic multipurpose X-ray diffractometer SmartLab) was used to perform 2θ / θ scanning with CuKα as the radiation source, tube voltage 40 kV, tube current 30 mA, step width 0.01°, and scan speed 10° / min. Phase identification was performed using PDF card numbers 01-075-0254 (3C-SiC) and 01-071-4034 (Al2O3) in the database (ICDD PDF-2). In addition, the weight concentration ratio of Al2O3 to SiC was determined by the Reference Intensity Ratio (RIR) method. In terms of the powder XRD pattern shown in FIG. 2, the diffraction line intensities of Al2O3 at 2θ values of 43.34° and 57.49° and the diffraction line intensity of 3C-SiC at 59.99° were obtained by peak fitting using X-ray analysis software (Rigaku, PDXL). The peak intensity ratio was referenced from the PDF card to estimate the intensity of the strongest line, and the mass concentration percentage was obtained using the RIR value. In the powder XRD measurement in this example, almost the same mass concentration percentage was obtained even when different diffraction lines of Al2O3 were used.
[0056] 1.4 Evaluation method for hydrogen production amount of photocatalyst powder The amount of hydrogen produced by the photocatalyst was measured and evaluated using the device shown in FIG. 3. 10 mg of photocatalyst powder and 10 ml of ultrapure water (>18 Ω·cm) were mixed to prepare a mixed liquid 24, and the mixed liquid 24 and a 10 mm stirring bar 29 were placed in a glass test tube 28 with a volume of 20 ml. A rubber stopper 26 was attached to the test tube 28, and a sealant 27 made of plastic paraffin film and vinyl tape was wrapped around the rubber stopper 26 and the test tube 28. Next, ultrasonic waves were applied to the inside of the test tube 28 and the mixed liquid 24 for 10 minutes using an ultrasonic cleaner. After that, while stirring the mixed liquid 24 at 300 rpm using a stirrer 25, N2 gas was bubbled into the inside of the test tube 28 and the mixed liquid 24 for 30 minutes to perform degassing. Then, a light irradiation area control plate 23 with a window of 3 cm in height and 1 cm in width was placed around the test tube 28 using aluminum foil. This is provided in the embodiment to eliminate the influence of external light such as fluorescent light and to make the irradiation light conditions constant. The light quantity of the solar simulator 21, which is the light source, was adjusted using a reference solar cell (Konica Minolta, AK-200) so as to be 1 sun. The stirrer 25 rotated the stirrer 29 at 1000 rpm, and the test tube was irradiated with simulated sunlight 22 from the solar simulator 21 through the window of the light irradiation area control plate 23. The simulated sunlight was irradiated for different irradiation times of 3 hours, 6 hours, and 18 hours. Here, irradiation from the side is shown in FIG. 3, but irradiation from the bottom, top, or slope may also be used. In addition, although the case where the solar simulator 21 is used as the light source has been described here, sunlight, a Hg lamp, a Xe lamp, or a halogen lamp may also be used. The gas components and concentration of the generated gas were analyzed by collecting 1 ml of the gas phase inside the test tube from the top of the rubber stopper with a microsyringe and using a gas chromatograph (Shimadzu, GC-2014) for which a calibration curve had been prepared in advance. The analysis results, the pressure of the gas phase (1 atm), the volume of the gas phase part of the test tube (9.056 mL), and the gas constant (R = 8.31 JK -1 Mol -1The amount of hydrogen produced was calculated using the gas equation of state (pV = nRT) from the temperature of the gas phase (293K) and the temperature of the gas phase (293K). The hydrogen production rate was calculated by linear fitting to the amount of hydrogen produced for each light irradiation time.
[0057] 2. Example 2 The same as in Example 1, except that the amount of carbon black mixed was 58 g, the amount of Al2O3 powder mixed was 8.16 g, and the amount of carbon black in the reduction step was 5.23 g.
[0058] 3. Example 3 The same as in Example 1, except that the amount of Al2O3 powder mixed was 10.88 g, and the amount of carbon black in the reduction step was 7.67 g.
[0059] 4. Example 4 The same as in Example 1, except that the amount of carbon black mixed was 58 g, the amount of Al2O3 powder mixed was 4.08 g, and the amount of carbon black in the reduction step was 3.81 g.
[0060] 5. Example 5 The same as in Example 1, except that the amount of carbon black mixed was 58 g, the amount of Al2O3 powder mixed was 2.72 g, and the amount of carbon black in the reduction step was 3.13 g.
[0061] 6. Comparative Example 1 The procedure was the same as in Example 1, except that no Al2O3 powder was mixed and no reduction step was performed.
[0062] 7. Comparative Example 2 The same as in Example 1, except that the amount of carbon black mixed was 58 g, the amount of Al2O3 powder mixed was 0.14 g, and the amount of carbon black in the reduction step was 5.18 g.
[0063] 8. Comparative Example 3 The same as in Example 1, except that the amount of carbon black mixed was 58 g, the amount of Al2O3 powder mixed was 1.36 g, and the amount of carbon black in the reduction step was 4.93 g.
[0064] Table 1 shows the Al / Si molar ratio in the mixture, the test conditions in the synthesis step and the reduction step, and the concentration of residual Al2O3 for Examples 1 to 5 and Comparative Examples 1 to 3.
[0065] [Table 1]
[0066] 9. Evaluation Results FIG. 4 shows the hydrogen generation rate for each of Examples 1 to 5 and Comparative Examples 1 to 3. As shown in FIG. 4, when the Al / Si ratio in the mixture is 0.04 or more (Examples 1 to 5), it was found that the hydrogen generation amount by water decomposition exceeds that using the 3C-SiC photocatalyst (Comparative Example 1) synthesized without mixing Al. Furthermore, it was found that the hydrogen generation rate is further improved when the Al / Si ratio is 0.08 or more. Here, as shown in Table 1, Example 2, in which the Al / Si ratio is 0.12, has a larger amount of residual Al2O3 than the other Examples. That is, in the hydrogen generation rate versus Al / Si ratio shown in FIG. 4, the hydrogen generation rate when the Al / Si ratio is 0.12 is lower than the hydrogen generation rate when the Al / Si ratio is 0.08 or 0.16, which is considered to be due to the relatively small amount of SiC present in the photocatalyst powder used for evaluating the amount of hydrogen generation.
[0067] 10. Additional Experiments and Results The photocatalyst of Example 1 was irradiated with light whose light intensity was adjusted to 50% of 1 sun in order to simulate a state of low solar light density, and the amount of hydrogen produced was evaluated. The results are shown in FIG. 5. As is clear from the results shown in FIG. 5, it was found that even when the light intensity was 50%, the same hydrogen production rate as when it was 100% could be obtained. In other words, it was found that the 3C-SiC photocatalyst of the example can produce a high amount of hydrogen by water decomposition even in an environment with low light density.
[0068] 11. Supplementary Information The reason why the photocatalytic activity improved with an increase in the Al / Si ratio can be considered as follows. That is, it is believed that the addition of impurities forms an impurity level, and the generation of electron-hole pairs through this improves the photocatalytic activity and increases the amount of hydrogen produced. When synthesizing 3C-SiC, nitrogen derived from the atmosphere is inevitably doped into the crystal, and when Al is incorporated into the 3C-SiC crystal, the charge can be compensated for by nitrogen as a donor and Al as an acceptor. As shown in Figure 4, when the Al / Si ratio is smaller than 0.04, the amount of hydrogen produced decreases, but when the Al / Si ratio is 0.04 or more, the amount of Al in the crystal increases, approaching a p-type semiconductor, and it is presumed that the doping effect of Al increases compared to the impurity doping effect of nitrogen, resulting in an increase in the amount of hydrogen produced. For the above reasons, it is interpreted that the Al / Si ratio in the mixture needs to be 0.04 or more in order to introduce an amount of Al into the crystal that can compensate for the nitrogen derived from the air in the 3C-SiC crystal. [Explanation of symbols]
[0069] 1 mixture 2. Graphite crucible 3. Molded insulation 4 High frequency induction coil 5. Vacuum Chamber 21 Solar Simulator 22 Simulated sunlight 23 Light irradiation area control plate 24 Mixture (water and photocatalyst) 25 Starla 26 Rubber stopper 27 Sealing material 28 Glass Test Tube 29 Stirring bar
Claims
1. mixing a silicon-containing oxide, a carbon source, and an aluminum-containing compound to obtain a mixture; heating the mixture to cause a carbothermal reduction reaction to obtain a product comprising 3C-SiC; and After the carbothermal reduction reaction, the product is heated in an oxidizing atmosphere to remove elemental carbon contained in the product, and then an acid washing treatment is performed to remove SiO 2 present in the product; Including, The molar ratio Al / Si of Al to Si contained in the mixture is 0.04 or more. A method for producing a 3C-SiC photocatalyst.
2. The atmosphere in which the mixture is heated to cause a carbothermal reduction reaction is an inert gas atmosphere. A method for producing the 3C-SiC photocatalyst according to claim 1.
3. The molar ratio Al / Si is 0.08 or more; A method for producing a 3C-SiC photocatalyst according to claim 1 or 2.
4. The temperature at which the mixture is heated is 1400° C. or higher and 1700° C. or lower. A method for producing a 3C-SiC photocatalyst according to any one of claims 1 to 3.
5. The aluminum-containing compound is Al 2 O 3 Using A method for producing a 3C-SiC photocatalyst according to any one of claims 1 to 4.
6. The silicon-containing oxide is SiO 2 Using A method for producing a 3C-SiC photocatalyst according to any one of claims 1 to 5.
7. Carbon black is used as the carbon source. A method for producing a 3C-SiC photocatalyst according to any one of claims 1 to 6.
8. A method for producing hydrogen using a 3C-SiC photocatalyst produced by the method according to any one of claims 1 to 7, producing hydrogen by irradiating the 3C-SiC photocatalyst with light while the 3C-SiC photocatalyst is in contact with water and decomposing water; Hydrogen production methods.
Citation Information
Patent Citations
Three-dimensional multistage structure nano silicon carbide, preparation method and application thereof
CN108285145A
Production of sic fine powder
JP1991054111A
Catalytic medium based on silicon carbide of high specific surface area in the form of granules with improved mechanical properties
JP2001507624A
HIGH CONVERSION EFFICIENCY SiC PHOTOELECTRODE, AND HYDROGEN PRODUCTION DEVICE USING THE SAME
JP2016145141A